AGRICULTURE AND PLANTATION MANAGEMENT TO SUPPORT THE EMPOWERMENT OF RURAL ISLAMIC BOARDING SCHOOL (CASE STUDY IN ISLAMIC BOARDING SCHOOL ABDUSSALAM) - Alhifni, Anas; Ahwarumi, Biyati (Program Studi Ekonomi Islam FEI UNIDA Bogor, 2018)
Islamic Boarding School Abdussalam is located in rural areas of West Kalimantan and has agriculture and plantation sectors. The purpose of this study is to find out how the agricultural management system implemented by Islamic Boarding School. This research uses qualitative approach with phenomenology analysis technique. The results show that agricultural and plantation conditions in Islamic Boarding School Abdussalam have been empowered and have given economic independence to Islamic Boarding School although only managed by traditional system, from both sectors of agriculture sector have bigger result than plantation sector. The proposed agriculture and plantation management design resulting from this research is modern management based on solving the main problems faced by both sectors, such as weakness of governance system, lack of profersional human resources, limited infrastructure and capital, through cooperation with some related institutions such as government, universities, and companies that are directly related to the agricultural and plantation sectors in Islamic Boarding School Abdussalam. Originality of research, such a study has never been done before because in this study described the management system and level of empowerment of agriculture and plantation Islamic Boarding School Abdussalam.Keywords: Islamic Boarding School Abdussalam, Empowerment, Agriculture and Plantation